Development of a Compact Wide-Slot Antenna for Early Stage Breast Cancer Detection Featuring Circular Array Full-View Geometry - Tiang, S. S.; Nik Anwar, N. S.; Ain, M. F.; Abdullah, M. Z. (Hindawi Publishing Corporation, 2014)
A novel planar type antenna printed on a high permittivity Rogers’ substrate is proposed for early stage microwave breast cancer detection. The design is based on a p-shaped wide-slot structure with 50Ω microstrip feeding circuit to eliminate losses of transmission.The design parameters are optimized resulting in a good reflection coefficient at −10 dB from4.5 to 10.9GHz. Imaging result using inhomogeneous breast phantom indicates that the proposed antenna is capable of detecting a 5mm size cancerous tumor embedded inside the fibroglandular region with dielectric contrast between the target and the surroundingmaterials ranging from 1.7:1 to 3.6:1.